Pengembangan Kurikulum Gereja Berbasis kontekstual: Tantangan dan Peluang di Era Modern - Gia, Petrus; Siringo Ringo, Samuel (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2026)
The development of the modern era, marked by technological advancement, social change, and shifts in people’s mindsets, requires the church to renew its faith-formation ministry. One important aspect that needs attention is the church curriculum so that it is not merely doctrinal but also relevant to the context of the congregation’s life. This article aims to examine the development of a contextual-based church curriculum by highlighting the challenges and opportunities that arise in the modern era. The method used is a theological and Christian education literature study, analyzing the concept of the church curriculum, the contextual approach, and the spiritual needs of today’s congregation. The study shows that the main challenges faced by the church include secularization, digital culture, pluralism, and the low involvement of younger generations in faith learning. However, the modern era also presents opportunities through the use of technology, participatory learning methods, and contextual approaches that connect God’s Word with the realities of daily life. The development of a contextual curriculum requires the church to understand the social, cultural, and psychological backgrounds of the congregation so that the faith-formation process becomes transformational rather than merely informational. Therefore, the church curriculum is expected to shape a mature, relevant, and applicable faith in everyday life. Abstrak Perkembangan zaman modern yang ditandai dengan kemajuan teknologi, perubahan sosial, serta pergeseran pola pikir masyarakat menuntut gereja untuk melakukan pembaruan dalam pelayanan pendidikan iman. Salah satu aspek penting yang perlu diperhatikan adalah kurikulum gereja, agar tidak hanya bersifat doktrinal tetapi juga relevan dengan konteks kehidupan jemaat. Artikel ini bertujuan mengkaji pengembangan kurikulum gereja berbasis kontekstual dengan menyoroti tantangan dan peluang yang muncul di era modern. Metode yang digunakan adalah studi literatur teologis dan pendidikan Kristen, dengan menganalisis konsep kurikulum gereja, pendekatan kontekstual, serta kebutuhan spiritual jemaat masa kini. Hasil kajian menunjukkan bahwa tantangan utama gereja meliputi pengaruh sekularisasi, budaya digital, pluralisme, serta rendahnya keterlibatan generasi muda dalam pembelajaran iman. Namun, era modern juga menghadirkan peluang berupa pemanfaatan teknologi, metode pembelajaran partisipatif, serta pendekatan kontekstual yang mampu menghubungkan firman Tuhan dengan realitas hidup jemaat. Pengembangan kurikulum kontekstual menuntut gereja untuk memahami latar belakang sosial, budaya, dan psikologis jemaat sehingga proses pendidikan iman menjadi transformasional, bukan sekadar informasional. Dengan demikian, kurikulum gereja diharapkan mampu membentuk iman yang dewasa, relevan, dan aplikatif dalam kehidupan sehari-hari.